GC-MS Assay to Ethanolic and Aquatic Extract of Mentha spicata L. leaves and Detection Effect of Extract as Antibacterial - Ahmed Jameel (University of Thi-Qar Journal of Science, 2025)
The analysis and identification of the chemical composition of the aqueous and ethanolic Mentha spicata L. extract by means of gaz chromatography and mass spectroscopy was realized in this paper. In addition, their antimicrobial activity was screened. From the leaf M. spicata, were separated, and determined their composition. The main components of ethanolic extract were Hexadecanoic acid, methyl ester (12.46%), Pentadecanoic acid (15.94%), Octadecanoic acid (6.11%), Methyl stearate (1.84%) and Phytol (28.06%). In Aquatic extract, the main components were Hexadecanoic acid, methyl ester (32.41%), Pentadecanoic acid (26.33%), Methyl stearate (12.33%) and Octadecanoic acid (7.58%). Furthermore, screening of the M. spicata extract for their antimicrobial activities reveals the highest activity of M. spicata alcoholic extract against Staphylococcus aureus, with an inhibition zone 15.8 ± 0.28 in 100% concentration and the highest activity of M. spicata aqueous extract against Pseudomonas aeruginosa, with an inhibition zone 14.0 ± 1.00 in 25% concentration. However, more research on the factors influencing the biosynthesis and bioactivity of chemical composition is needed as aqueous and ethanolic extract have gained important applications in food and pharmaceuticals industry.